2014
DOI: 10.5455/2320-6012.ijrms20141171
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis between single incision and conventional laparoscopic appendectomy for acute appendicitis

Abstract: Acute appendicitis is a surgical emergency causing significant mortality and morbidity. 1 In other words it is referred as an acute inflammatory condition of the appendix. Most cases require immediate action to avoid unnecessary complications through surgical procedures like open or laparoscopic appendectomy. 2 Appendicitis is one of the leading cause for abdominal surgical emergencies. Worldwide statistics reveal its incidence is more than 8%. 3 The majority of the patients suffering with this mainly present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
1
1
0
1
Order By: Relevance
“…Fischer et al 15 reported intra-abdominal collection as similar complications in both groups (1.4 vs. 1.8%). Similarly, several comparative studies, systematic reviews and meta-analyses have not found significant differences in the development of postoperative intra-abdominal collection, which is consistent with our study 9,10,16,17 .…”
Section: Discussionsupporting
confidence: 93%
“…Fischer et al 15 reported intra-abdominal collection as similar complications in both groups (1.4 vs. 1.8%). Similarly, several comparative studies, systematic reviews and meta-analyses have not found significant differences in the development of postoperative intra-abdominal collection, which is consistent with our study 9,10,16,17 .…”
Section: Discussionsupporting
confidence: 93%
“…Fischer, et al 15 informaron complicaciones como colección intraabdominal similares en los dos grupos (1.4 vs. 1.8%). De igual manera, numerosos estudios comparativos, revisiones sistemáticas y metaanálisis no han encontrado diferencias significativas en la formación de colección intraabdominal posoperatoria, en concordancia con nuestro estudio 9,10,16,17 .…”
Section: Discussionunclassified
“…[2] In addition to open and laparoscopic surgical methods, single-incision laparoscopic surgery (SILS) and natural orifice transluminal endoscopic appendectomy (NOTES) methods were also described for surgical treatment of acute appendicitis. [1,[3][4][5] Clo-Cite this article as: Çelik Y, Erbil OA. Comparison of methods for closure of appendix stump during laparoscopic appendectomy using endoloops: Single surgeon experience.…”
Section: Introductionmentioning
confidence: 99%